Assessment of multidrug resistance, clonality and virulence in non-PCV-13 Streptococcus pneumoniae serotypes in Canada, 2011–13. (11th March 2015) - Golden, Alyssa R.; Adam, Heather J.; Gilmour, Matthew W.; Baxter, Melanie R.; Martin, Irene; Nichol, Kimberly A.; Demczuk, Walter H. B.; Hoban, Daryl J.; Zhanel, George G.
Abstract: Objectives: Serotype replacement in Streptococcus pneumoniae following the implementation of a new vaccine has been associated with the emergence of non-vaccine serotypes as prominent causes of invasive pneumococcal disease (IPD). The aim of this study was to characterize specific non-PCV-13 serotypes 15A, 22F, 33F and 35B from IPD, isolated in Canada post-PCV-13 introduction in 2010. Methods: Of 3802 IPD isolates collected from across Canada in 2011–13, 18.4% were found to be serotypes 15A, 22F, 33F and 35B. These 699 isolates were subjected to antimicrobial susceptibility testing, PFGE, MLST, molecular detection of pneumococcal pili and comparison with Pneumococcal Molecular Epidemiology Network (PMEN) clones. Results: This study demonstrated clonal spread of specific STs, including MDR ST63 and its Sweden 15A -25-related variants, the increasingly common ST433 and a variant of piliated, penicillin-non-susceptible ST558, related to PMEN clone Utah 35B -24 (ST377). New STs of serotype 33F were identified. Several potential capsular switching events were identified within these serotypes. Conclusions: Non-PCV-13 serotype 22F is increasing in Canada through the rapid clonal expansion of ST433. Numerous new STs associated with serotype 33F indicate the potential divergence of the serotype. Serotypes 15A and 35B in Canada are related to international clones of S. pneumoniae .